Research on Pure Modes I and II and Mixed-Mode (I/II) Fracture Toughness of Geopolymer Fiber-Reinforced Concrete - Sundaravadivelu Karthik; Kaliyaperumal Saravana Raja Mohan; Gunasekaran Murali; Gobinath Ravindran (Advances in Civil Engineering)
The unsustainable use of resources and the rising demand for traditional concrete have disrupted ecological equilibrium, necessitating the adoption of a more appropriate and long-lasting alternative. One such substitute for cement in concrete production is geopolymer concrete, although this material is prone to cracking and fracturing due to its low tensile strength, leading to costly repairs or even structural collapse. Fiber-reinforced concrete has recently been widely adopted as a construction material to counteract these issues. This research examined the crack proliferation and fracture toughness of geopolymer concrete comprising different fibers using a cracked Brazilian disc. Four different fibers were used, such as polypropylene and steel fiber (short and long), at a dosage of 1.5% by volume. Fracture toughness was computed for various modes (I, II, and I/II) of fractures, and crack propagation from cracked specimens was studied. A different angle of inclination (0, 15, 28, 83, 60, 75, and 90 degrees) was used to conduct the Brazilian disc test on the specimens with respect to the preexisting crack direction. The findings indicate that the increasing loading angle increased the load-carrying capacity. The fracture toughness values of specimens under all three modes ranged from 0.26 to 1.75 MPa.m1/2. Additionally, long polypropylene and steel fibers exhibit higher fracture toughness than short fibers.